The Influence of Leadership, Work Environment and Welfare Levels on Employee Work Productivity - Anditha, Nur (Borong Newinera Publisher, 2025)
This study aims to analyze the impact of leadership, work environment, and welfare level on employee work productivity at the village office. The research was conducted at the Tanah Loe and Gantarangkeke village offices, using multiple linear regression analysis techniques. This study is quantitative and uses questionnaires as the data collection source. The study involved 52 respondents, consisting of civil servants (ASN) and honorary staff. The results of this study indicate that, There is no significant influence of leadership on employee work productivity. This is evidenced by the acceptance of H0 and the rejection of H1, as the significance value is P = 0.749 > 0.05, 2) There is no significant influence of the work environment on employee work productivity. This is evidenced by the acceptance of H0 and the rejection of H2, as the significance value is P = 0.185 > 0.05. There is a significant influence of the level of employee welfare on work productivity. This is evidenced by the rejection of H0 and the acceptance of H3, as the significance value is P = 0.000 < 0.05. Based on the results of the multiple regression test, the Model Summary shows an R² value of 0.827. This means that the independent variables leadership, work environment, and employee welfare can predict the dependent variable, employee work productivity, by 82.7%. The remaining 17.3% is explained by other factors